Testing the Conditional Correlations and Volatility Spillovers between US and ASEAN Islamic Stock Markets: A Multivariate GARCH Analysis - Sutan Emir Hidayat; Muhammad Rizky Prima Sakti; Abdullah Al-Hadrami (Global Review of Islamic Economics and Business, 2022)
This study examines the conditional correlations and volatility spillovers between the US and ASEAN Islamic stock markets. The empirical design uses MSCI (Morgan Stanley Capital International) Islamic indexes as it adopted stringent restrictions to include companies in the sharia list. By using three multivariate GARCH models (BEKK, diagonal VECH, and CCC model), we find evidence of returns and volatility spillovers from the US to the ASEAN Islamic stock markets. However, as the estimated time-varying conditional correlations and volatilities indicate there is still room for diversification benefits, particularly in the single markets. The Islamic MSCI of Thailand, Indonesia, and Singapore are less correlated to the US MSCI Islamic index. The implication is that foreign investors may benefit from the reduction of risk by adding Islamic stocks in those countries.